A Review of Multi‐Order Diffraction Beams: From Phase Gradient Metasurface to Metagratings - Yuxiang Wang; Yueyi Yuan; Kuang Zhang (Advanced Physics Research)
Abstract Metasurfaces have attracted progressive attention as 2D metamaterials in recent years. Due to the ability to manipulate the phase, amplitude, and polarization of electromagnetic waves, metasurfaces have become a feasible way to control the wavefront. Here, two main platforms for exciting multi‐order diffraction beams in the far field based on metasurfaces, i.e., phase gradient metasurfaces (PGMs) and metagratings (MGs) are reviewed. First, the concept of generalized Snell's law (GSL) as well as the related works are presented. Then the connection between GSL and diffraction law is elaborated. The multi‐order diffraction methods based on the combination of the two principles are introduced. Following the discussion on several kinds of PGMs platforms for achieving multiple beams, the physical mechanisms of MGs are reviewed and recent progress is summarized. Finally, the typical challenges are outlined and the future development directions are prospected.